“If every porkchop were perfect, we wouldn’t have hotdogs”: how Cartoon Network's Steven Universe conceptualises and communicates the issues of mental health - Fong, Wai Kei (Nanyang Technological University, 2025)
Steven Universe depicts the eponymous protagonist’s negotiations not only with his personal life but also with threats from the Gem Homeworld. Hailed as the first Cartoon Network property created by an openly queer woman, the bulk of the show’s existing literature centres on themes of queerness and gender. While these will still be discussed due to the intersectionality of queerness and mental health, I will primarily explore how the show conceptualises and communicates issues of mental health for its audiences, appealing to both its intended younger audience and the inner child of older viewers. Just like how queer theory’s queer temporality framework challenges conventional linear childhood narratives, the show confronts normative societal expectations of healing too. Some key themes discussed include identity, emotional regulation, interpersonal relationships, trauma, and therapy. I argue that the show emphasises how healing is not only about progressing forward but also spotlights how one navigates varying degrees of fluctuating emotions. By way of examining the development of these themes, I will examine its visual aesthetics, narrative structures, and audio-visual elements, delving into the importance of the creative decisions behind the scenes within the production team behind the show.